Health-related quality of life with pembrolizumab or placebo plus chemotherapy with or without bevacizumab for persistent, recurrent, or metastatic cervical cancer (KEYNOTE-826): a randomised, double-blind, placebo-controlled, phase 3 trial - Monk, BJ (2023)
Background: In the KEYNOTE-826 study, the addition of the anti-PD-1 monoclonal antibody pembrolizumab to chemotherapy with or without bevacizumab improved overall survival and progression-free survival (primary endpoints) versus placebo plus chemotherapy with or without bevacizumab, with manageable toxicity, in patients with persistent, recurrent, or metastatic cervical cancer. In this Article, we report patient-reported outcomes (PROs) from KEYNOTE-826. Methods: KEYNOTE-826 is a multicentre, randomised, phase 3 trial in 151 cancer treatment centres in 19 countries. Eligible patients were aged 18 years or older with persistent, recurrent, or metastatic cervical cancer not previously treated with systemic chemotherapy (previous radiosensitising chemotherapy was allowed) and not amenable to curative treatment and had an Eastern Cooperative Oncology Group performance status of 0 or 1. Patients were randomly assigned (1:1) centrally by means of an interactive voice response system in a double-blind manner to receive either pembrolizumab 200 mg or placebo every 3 weeks intravenously for up to 35 cycles plus chemotherapy (paclitaxel 175 mg/m2 plus cisplatin 50 mg/m2 or carboplatin area under the curve 5 mg/mL per min, intravenously) with or without bevacizumab 15 mg/kg every 3 weeks intravenously. Randomisation (block size of 4) was stratified by metastatic disease at diagnosis, planned bevacizumab use, and PD-L1 combined positive score. Patients, investigators, and other study personnel involved in study treatment administration or clinical evaluation of patients were unaware of treatment group assignments. PRO instruments were the EORTC Quality-of-Life-Core 30 (QLQ-C30), the EORTC cervical cancer module (QLQ-CX24), and the EuroQol-5 dimension-5 level (EQ-5D-5L) visual analogue scale, each collected before treatment at cycles 1–14 and every other cycle thereafter. Primary endpoints were overall survival and progression-free survival per RECIST version 1.1 by investigator review. Change from baseline in QLQ-C30 global health status (GHS)–quality of life (QoL) was a prespecified secondary endpoint and was assessed in the PRO full analysis population (all patients who received at least one dose of study treatment and completed at least one post-baseline PRO assessment). Other PRO analyses were protocol-specified exploratory endpoints. The study is registered with ClinicalTrials.gov, NCT03635567, and is ongoing. Findings: Between Nov 20, 2018, and Jan 31, 2020, of 883 patients screened, 617 were randomly assigned (pembrolizumab group, n=308; placebo group, n=309). 587 (95%) of 617 patients received at least one dose of study treatment and completed at least one post-baseline PRO assessment and were therefore included in the PRO analyses (pembrolizumab group, n=290; placebo group, n=297). Median follow-up was 22·0 months (IQR 19·1–24·4). At week 30, QLQ-C30 completion was 199 (69%) of 290 patients in the pembrolizumab group and 168 (57%) of 297 patients in the placebo group; compliance was 199 (94%) of 211 and 168 (90%) of 186, respectively. The least squares mean change in QLQ-C30 GHS–QoL score from baseline to week 30 was −0·3 points (95% CI −3·1 to 2·6) in the pembrolizumab group and −1·3 points (−4·2 to 1·7) in the placebo group, with a between-group difference in least squares mean change of 1·0 point (95% CI −2·7 to 4·7). Median time to true deterioration in GHS–QoL was not reached (NR; 95% CI 13·4 months–NR) in the pembrolizumab group and 12·9 months (6·6–NR) in the placebo group (hazard ratio 0·84 [95% CI 0·65–1·09]). 122 (42%) of 290 patients in the pembrolizumab group versus 85 (29%) of 297 in the placebo group had improved GHS–QoL at any time during the study (p=0·0003). Interpretation: Addition of pembrolizumab to chemotherapy with or without bevacizumab did not negatively affect health-related quality of life. Along with the efficacy and safety results already reported from KEYNOTE-826, these data support the benefit of pembrolizumab and the value of immunotherapy in patients with recurrent, persistent, or metastatic cervical cancer. Funding: Merck Sharp & Dohme.